PCSK9 regulates the efficacy of immune checkpoint therapy in lung cancer - Gao, Xiang; Yi, Ling; Jiang, Chang; Li, Shuping; Wang, Xiaojue; Yang, Bin; Li, Weiying; Che, Nanying; Wang, Jinghui; Zhang, Hongtao; Zhang, Shucai (Frontiers in Immunology, 2023)
Proprotein convertase subtilisin/kexin type 9 (PCSK9) secreted by tumors was reported as a deleterious factor that led to the reduction of lymphocyte infiltration and the poorer efficacy of ICIs in vivo. This study aimed to explore whether PCSK9 expression in tumor tissue could predict the response of advanced non-small cell lung cancer (NSCLC) to anti-PD-1 immunotherapy and the synergistic antitumor effect of the combination of the PCSK9 inhibitor with the anti-CD137 agonist. One hundred fifteen advanced NSCLC patients who received anti-PD-1 immunotherapy were retrospectively studied with PCSK9 expression in baseline NSCLC tissues detected by immunohistochemistry (IHC). The mPFS of the PCSK9lo group was significantly longer than that of the PCSK9hi group [8.1 vs. 3.6 months, hazard ratio (HR): 3.450; 95% confidence interval (CI), 2.166-5.496]. A higher objective response rate (ORR) and a higher disease control rate (DCR) were observed in the PCSK9lo group than in the PCSK9hi group (54.4% vs. 34.5%, 94.7% vs. 65.5%). Reduction and marginal distribution of CD8+ T cells were observed in PCSK9hi NSCLC tissues. Tumor growth was retarded by the PCSK9 inhibitor and the anti-CD137 agonist alone in the Lewis lung carcinoma (LLC) mice model and further retarded by the PCSK9 inhibitor in combination with the CD137 agonist with long-term survival of the host mice with noticeable increases of CD8+ and GzmB+ CD8+ T cells and reduction of Tregs. Together, these results suggested that high PCSK9 expression in baseline tumor tissue was a deleterious factor for the efficacy of anti-PD-1 immunotherapy in advanced NSCLC patients. The PCSK9 inhibitor in combination with the anti-CD137 agonist could not only enhance the recruitment of CD8+ and GzmB+ CD8+ T cells but also deplete Tregs, which may be a novel therapeutic strategy for future research and clinical practice.